2004
DOI: 10.1016/j.jhsa.2004.04.025
|View full text |Cite
|
Sign up to set email alerts
|

The terminal tendon of the digital extensor mechanism: Part II, kinematic study

Abstract: Only DIP and PIP joints affect TT excursion; hence these are the main joints to be immobilized to protect TT repair. The middle finger TT showed the least tolerance to lengthening with potential for mallet deformity. Joint flexion deformity is proportional to tendon lengthening. Only 1 mm of TT lengthening results in approximately 25 degrees of DIP joint extension lag, and 4 mm of TT lengthening results in DIP joint flexion deformity greater than 60 degrees . Even 1 mm of TT shortening will seriously restrict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 10 publications
(7 reference statements)
3
25
0
1
Order By: Relevance
“…The best results were in the younger patients; the worse results were in those with bony mallet finger, likely because of greater tendon shortening after resection of the bone fragment. Schweitzer and Rayan's experimental work has shown that it is very difficult to reinsert the terminal extensor tendon if it is more than 1 mm retracted [19]. Similar results were obtained by Ulkür et al who reinserted the terminal tendon on the P3 base with a bone anchor [25] and with pull-out and pull-in suture techniques [26,27].…”
Section: Surgical Treatmentsupporting
confidence: 55%
See 1 more Smart Citation
“…The best results were in the younger patients; the worse results were in those with bony mallet finger, likely because of greater tendon shortening after resection of the bone fragment. Schweitzer and Rayan's experimental work has shown that it is very difficult to reinsert the terminal extensor tendon if it is more than 1 mm retracted [19]. Similar results were obtained by Ulkür et al who reinserted the terminal tendon on the P3 base with a bone anchor [25] and with pull-out and pull-in suture techniques [26,27].…”
Section: Surgical Treatmentsupporting
confidence: 55%
“…Scheitzer and Rayan have shown that 1 mm of tendon lengthening triggers a 25-degree DIP extensor lag and that 4 mm of lengthening leads to more than 60 degrees lag [19].…”
Section: Clinical Presentation and Functional Impairmentmentioning
confidence: 99%
“…Moreover, these authors reported that in the DIP resting position, the intact tendon showed at a 22° angle. Likewise, the TT has been reported to exhibit an average 25° angle with a 1‐mm lengthening and a 36° angle with a 2‐mm lengthening 8. As little as 1 mm of TT shortening can result in a disturbance of the DIP joint balance 8.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical technique presented in this study is made possible by the unique characteristic of the pulp. Numerous fibrous septa of the pulp allows for enough traction force needed for good visualisation for anatomical reduction of the bony mallet finger [16][17][18]. The technique introduced in this study has the following advantages:…”
Section: Discussionmentioning
confidence: 99%